Review of The Institutional View on The Liberalization and Management of Capital Flows : Background Note on Principles for the Design of Measures to Address Systemic Risks from FX Mismatches - Kang, Heedon (Policy Papers; Policy Paper, 2022)
This note describes the key principles for the design and implementation of preemptive CFM/MPMs. These measures should be designed to be effective-so they achieve their intended goal and are not easily circumvented-and efficient-so they minimize distortions and costs. Preemptive CFM/MPMs should be targeted, calibrated to risks, transparent, and as temporary as possible. The appropriate design depends on country circumstances, such as institutional and legal constraints, as well as the precise source of the vulnerability. Where measures that do not discriminate by residency are available and effective, they should be preferred.